Thermoplastic molding of silk protein composite plastic toothbrush handles with on-demand degradability - Wu, Junqi; Wiggins, Rodrick D.; Weaver, Casey H.; Kugel, Gerard; Kaplan, David L. (Frontiers in Sustainability, 2023)
Toothbrush handles made from synthetic polymers like polypropylene and polyethylene accumulate in the environment at an annual rate of 1 billion devices per year and without significant degradation, resulting in severe burdens particularly in marine environments. Herein, we report a new process to generate these plastic handles using natural, biopolymer-based components using a direct thermoplastic molding approach, that also offers on-demand degradation of the materials. The materials are prepared directly from whole silk cocoons that are thermoplastically transformed into biodegradable plastic parts for consumer needs, here in the form of toothbrush handles; either with silk alone or in combination with other natural sourced materials such as cellulose, chitosan and hydroxyapatite. We demonstrate the on-demand degradation of these bioplastics in different ways, using natural exogenous protease digestion either offered through soil exposure of the silk based plastics or via unique on-demand activation of proteases sequestered in the plastic materials to drive the degradation on-demand (hydration). The approaches described here demonstrate a new approach to bio-plastic formation and degradation from biopolymers that offers widespread options for future consumer materials with a focus on sustainability.